Acting and performing: influences of manager emotional intelligence. Issue 1 (12th February 2018) - Prati, L. Melita; Karriker, Joy H.
Abstract : Purpose: The purpose of this paper is to examine the predictive role of manager emotional intelligence (MEI) with regard to emotional labor efforts and outcomes relationships. Testing evaluated the influence of MEI on the effects of emotional labor activities employed by subordinates (e.g. surface and active deep acting). Design/methodology/approach: Relationships were examined between the emotional labor efforts employed by subordinates and their levels of depressed mood, as well as the supervisory leaders' evaluations of the subordinates' emotional performance resulting indirectly and directly from the emotional labor activities. Specifically, hypotheses that MEI will influence the performance of emotional labor and the effects of such activities on depressed mood and emotional performance were tested. Findings: Findings indicate that MEI moderates the impact of depressed mood on emotional performance. Originality/value: This research adds to the emotional intelligence literature and enhances practical understanding of how organizations dependent on relationship-oriented, successful customer care can sponsor employee actions that facilitate results.